The directionality of anxiety and gaming disorder: An exploratory analysis of longitudinal data from an Australian youth population - Kim, Seungyeon; Champion, Katrina E.; Gardner, Lauren A.; Teesson, Maree; Newton, Nicola C.; Gainsbury, Sally M. (Frontiers in Psychiatry, 2022)
Gaming activities among adolescents have increased during the COVID-19 pandemic, bringing with it a growing concern for the potential harms of gaming and its risk factors. Anxiety is frequently linked with gaming disorder, but studies on the association between anxiety and gaming are mostly cross-sectional in design. Longitudinal studies that explore risk factors associated with gaming disorder are sparce and the trajectories of gaming disorder remain unclear. To address this paucity, the present study analyzed a large longitudinal dataset with a 12-month follow-up of 4,968 Australian adolescents (ages 13-14) during the pandemic. Logistic regression and multiple regression analyses were conducted to investigate the temporal relationships between anxiety, gaming frequency, the amount of money spent on content within video games, and gaming disorder. Prevalence rates for gaming disorder in adolescents aged 13 and 14 were 15% and 16%, respectively. The results showed an alarming prevalence rate of gaming disorder in adolescents aged 13 and 14 during the pandemic. The regression models indicated a bidirectional relationship between anxiety and gaming disorder symptoms, where one predicted the other 12 months later. When modelled together, anxiety and gaming frequency significantly predicted gaming disorder symptoms after 12 months. Overall, the findings suggest that early adolescents may be a more vulnerable to developing gaming disorder and highlight the importance of addressing the interactions between risk factors and gaming disorder in the treatment of gaming disorder.